Some results on s-fan h designs with six groups - Meng, Zhaoping (Utilitas Mathematica, 2018)
An H(n,g4,3) is called 8-fan if its block set can be partitioned into disjoint subsets β1 β2 β3 and A, such that every B, is the block set of a GDD(2,4ign) of type gn for 1 < i < s. In this paper, We give an infinite class of s-fan H(6,p,4,3)s. As an application, we also give an infinite class of nonuniform group divisible 3-designs with seven groups. © 2018 Utilitas Mathematica Publishing Incorporated. All rights reserved.